A genetically encoded far‐red fluorescent calcium ion biosensor derived from a biliverdin‐binding protein. (28th September 2022) - Hashizume, Rina; Fujii, Hajime; Mehta, Sohum; Ota, Keisuke; Qian, Yong; Zhu, Wenchao; Drobizhev, Mikhail; Nasu, Yusuke; Zhang, Jin; Bito, Haruhiko; Campbell, Robert E.
Abstract: Far‐red and near‐infrared (NIR) genetically encoded calcium ion (Ca 2+ ) indicators (GECIs) are powerful tools for in vivo and multiplexed imaging of neural activity and cell signaling. Inspired by a previous report to engineer a far‐red fluorescent protein (FP) from a biliverdin (BV)‐binding NIR FP, we have developed a far‐red fluorescent GECI, designated iBB‐GECO1, from a previously reported NIR GECI. iBB‐GECO1 exhibits a relatively high molecular brightness, an inverse response to Ca 2+ with Δ F / F min  = −13, and a near‐optimal dissociation constant ( K d ) for Ca 2+ of 105 nM. We demonstrate the utility of iBB‐GECO1 for four‐color multiplexed imaging in MIN6 cells and five‐color imaging in HEK293T cells. Like other BV‐binding GECIs, iBB‐GECO1 did not give robust signals during in vivo imaging of neural activity in mice, but did provide promising results that will guide future engineering efforts. Significance: Genetically encoded calcium ion (Ca 2+ ) indicators (GECIs) compatible with common far‐red laser lines (~630–640 nm) on commercial microscopes are of critical importance for their widespread application to deep‐tissue multiplexed imaging of neural activity. In this study, we engineered a far‐red excitable fluorescent GECI, designated iBB‐GECO1, that exhibits a range of preferable specifications such as high brightness, large fluorescence response to Ca 2+, and compatibility with multiplexed imaging in mammalian cells.